Novel Carbon Dioxide Utilization Technologies: A Means to an End - Warsi, Yusra; Kabanov, Vladimir; Zhou, Peter; Sinha, Apoorv (Frontiers in Energy Research, 2020)
Carbon dioxide removal (CDR) is an essential feature of climate mitigation. With current techniques falling short in terms of performance, cost, and environmental integrity, novel CO2 utilization has the potential to create a multi-billion dollar commodity market that is capable of sequestering large amounts of CO2 from the atmosphere. To achieve this, significant development in terms of government funding, policy change, and research is needed. This review highlights the current state of novel CO2 utilization technologies. The paper evaluates their future prospects by drawing parallels with two successfully developed hardware-heavy technologies of the last 50 years, namely the solar and the automobile industries. Both technologies have had radically different commercialization pathways, and offer important insights on facilitating and accelerating the development of novel CO2 utilization technologies to meet critically relevant climate targets.